The Effect of Career Development and Organizational Commitment on Employee Performance Through Extrinsic Motivation at PT Bank Sumut Kantor Cabang Koordinator Medan - Nurul Huda Chasanah; Ritha F. Dalimunthe; Prihatin Lumbanraja (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
Employee performance is a strategic factor in the success of regional banking organizations that are oriented towards service and achieving business targets. However, empirical evidence at PT Bank Sumut Kantor Cabang Koordinator Medan, indicates that employee performance tends to stagnate in the "Good" category during the 2021–2024 period. This condition is thought to be related to career development that is not yet optimally structured, organizational commitment that has not been fully actualized in work behavior, and inadequate extrinsic motivation. This study aims to analyze the effect of career development and organizational commitment on employee performance through extrinsic motivation as a mediating variable. The study used a quantitative approach with a survey method of employees at PT Bank Sumut Kantor Cabang Koordinator Medan. Data were analyzed using Structural Equation Modeling. The results show that career development and organizational commitment influence extrinsic motivation, and extrinsic motivation plays a role in improving employee performance and mediating the relationship between variables. These findings strengthen the role of extrinsic motivation as an important mechanism in bridging human resource policies and employee performance in regional banking.